Development of STEM-Based Digital Handouts for Nuclear Physics Introduction Courses During the Covid-19 Pandemic - Murniati Murniati; Apit Fathurrohman; Yurindah Letari (Postgraduate, University of Mataram, 2022)
The Covid-19 pandemic has caused changes in the world educational system. The pandemic caused a rapid transition from face-to-face lectures to online lectures. The times of the Covid-19 pandemic or what is often called “the New Normal